Macroeconomic Developments in the Baltics, Russia, and Other Countries of the Former Soviet Union, 1992-97 - Valdivieso, Luis (Occasional Papers; Occasional Paper ;, 1999)
This paper discusses the significant overall progress with macro stabilization of these transition countries during 1992-1997. While average inflation declined steadily since 1992, output fell significantly for many of these countries during this period, and it was not unti 1996-97 that as a group they experienced positive growth, financial policies, the current account, competitiveness, debt-and non-debt-creating capital flows, and the initial impact of the Asian crisis.